PROFESIONALISME GURU PAI YAYASAN NURUL ILMI DALAM KEWAJIBAN BELAJAR DAN MENGAJAR PERSPEKTIF AL-QUR’AN DAN HADIS - Yulia Wahyuni; Lia Laili Rosadah; Cukup Islamiarso; Alimron; Suharmon (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the professionalism of Islamic Religious Education (PAI) teachers at the Nurul Ilmi Foundation by emphasizing the obligation to learn and teach as reflected in the Qur’an and Hadith. In the Islamic perspective, a teacher is not merely a transmitter of knowledge but also a lifelong learner who must continually enhance their competence, insight, and professional ethics. Therefore, this research focuses on how PAI teachers are able to balance professional development activities such as pursuing higher education, attending training and workshops, and participating in scientific forums with their primary responsibility in the classroom teaching process. The study employs a qualitative method with a case study approach, involving in-depth interviews, classroom observations, and documentation analysis of teachers’ self-development activities. The data were analyzed descriptively by linking teachers’ professional practices to the principles of the Qur’an and Hadith, which emphasize the obligation to seek knowledge, teach it, and uphold the trust of education. The results reveal that PAI teachers at the Nurul Ilmi Foundation successfully maintain a balance between professional and spiritual responsibilities, ensuring that teaching practices remain high-quality, innovative, and grounded in Islamic values. This study recommends a model of teacher professionalism that integrates religious commitment and continuous learning, fostering Islamic character development within education.